Hyperacute perfusion imaging before pediatric thrombectomy: analysis of the Save ChildS Study - Lee, Sarah; Mlynash, Michael; Christensen, Soren; Jiang, Bin; Wintermark, Max; Sträter, Ronald; Broocks, Gabriel; Grams, Astrid; Nikoubashman, Omid; Morotti, Andrea; Trenkler, Johannes; Möhlenbruch, Markus Alfred; et al. (Neurology, 2023)
Background and Objectives Perfusion imaging can identify adult patients with salvageable brain tissue who would benefit from thrombectomy in later time windows. The feasibility of obtaining hyperacute perfusion sequences in pediatric stroke is unknown. The aim of this study was to determine whether contrast perfusion imaging delayed time to treatment and to assess perfusion profiles in children with large vessel occlusion stroke. - Methods The Save ChildS retrospective cohort study (January 2000-December 2018) enrolled children (1 month-18 years) with stroke who underwent thrombectomy from 27 European and U.S. stroke centers. This secondary analysis included patients with anterior circulation occlusion and available imaging for direct review by the neuroimaging core laboratory. Between-group comparisons were performed using the Wilcoxon rank-sum exact test for continuous variables or Fisher exact test for binary variables. Given the small number of patients, evaluation of perfusion imaging parameters was performed descriptively only. - Results Of 33 patients with available neuroimaging, 15 (45.4%) underwent perfusion (CT perfusion n = 6; MR perfusion n = 9); all were technically adequate. The median time from onset to recanalization did not differ between groups {4 hours (interquartile range [IQR] 4-7.5) perfusion+; 3.4 hours (IQR 2.5-6.5) perfusion-, p = 0.158}. Target mismatch criteria were met by 10/15 (66.7%) patients and did not correlate with reperfusion status or functional outcome. The hypoperfusion intensity ratio (HIR) was favorable in 11/15 patients and correlated with older age but not NIHSS, time to recanalization, or stroke etiology. Favorable HIR was associated with better functional outcome at 6 months (Pediatric Stroke Outcome Measure 1.0 [IQR 0.5-2.0] vs 2.0 [1.5-3.0], p = 0.026) and modified Rankin Scale 1.0 [0-1] vs 2.0 [1.5-3.5], p = 0.048) in this small sample. - Discussion Automated perfusion imaging is feasible to obtain acutely in children and does not delay time to recanalization. Larger prospective studies are needed to determine biomarkers of favorable outcome in pediatric ischemic stroke and to establish core and penumbral thresholds in children.
Zuerst veröffentlicht: 21. Dezember 2022
Gesehen am 27.07.2023